Attack : with a National 'Clean Throat' campaign / by A, Corbett-Smith - Corbett-Smith, Arthur, 1879-
1929-10 1929 1920s 6 pages [Picture] ATTACK! with a NATIONAL 'CLEAN THROAT' CAMPAIGN by A. Corbett-Smith AUTHOR OF "NELSON THE MAN" "RIDERS OF THE AIR" "THE RETREAT FROM MONS" "CHINA AND HER PEOPLE" ETC. 200/B/3/2/C693/3/13